EKSTRAKSI DAN IDENTIFIKASI SENYAWA ANTOSIANIN DARI JANTUNG PISANG RAJA (Musa x paradisica L.) SERTA UJI AKTIVITAS ANTIOKSIDANNYA - Jessica Alvionita; Djaswir Darwis; Mai Efdi (Universitas Andalas, 2016)
Anthocyanin coumpound have been successfully extracted from plantain bud (Musa x paradisiaca L) which can used as natural colorant and antioxidant. Coumpound anthocyanin exracted using maceration method with solvent ethanol that has been acidified with acetic acid and citric acid until pH 1,5. The extract anthocyanin is identified by UV-Vis spectrophotometer (260-800 nm) and retrieved two peaks that is 277 nm (UV) and 533 nm (Visible). Further treatment is carried out with KCKT-DAD at a wavelength 516 nm. Anthocyanin treatment given temperature and pH. Total anthocyanin monomeric obtained for ethanol + acetic acid was 30,22 mg/L; ethanol + citric acid was 18,20 mg/L. The warming influence of the anthocyanin compound lead to degradation of color is highest for ethanol + acetic citric on temperature 100oC with percentage degradation of 61,97 %. The antioxidant activity of the extract was measured by 1,1- difenil-2-pikrilhidrazil (DPPH) the result showed that the anthocyanin extracts from Plantain bud has antioxidant activity ethanol + acetic citric acid extract is very active as an antioxidant with IC50 Â values of 3,74 mg/L.